Survival analysis of HDR brachytherapy versus reoperation versus temozolomide alone: a retrospective cohort analysis of recurrent glioblastoma multiforme - Archavlis, Eleftherios (BMJ Publishing Group, 2013)
OBJECTIVES: Tumour recurrence of glioblastoma multiforme (GBM) after initial treatment with surgical resection, radiotherapy and chemotherapy is an inevitable phenomenon. This retrospective cohort study compared the efficacy of interstitial high dose rate brachytherapy (HDR-BRT), re-resection and sole dose dense temozolomide chemotherapy (ddTMZ) in the treatment of recurrent glioblastoma after initial surgery and radiochemotherapy. DESIGN: Retropective cohort study. SETTING: Primary level of care with two participating centres. The geographical location was central Germany. PARTICIPANTS: From January 2005 to December 2010, a total of 111 patients developed recurrent GBM after initial surgery and radiotherapy with concomitant temozolomide. The inclusion criteria were as follows: (1) histology-proven diagnosis of primary GBM (WHO grade 4), (2) primary treatment with resection and radiochemotherapy, and (3) tumour recurrence/progression. INTERVENTIONS: This study compared retrospectively the efficacy of interstitial HDR-BRT, re-resection and ddTMZ alone in the treatment of recurrent glioblastoma. PRIMARY AND SECONDARY OUTCOME MEASURES: Median survival, progression free survival and complication rate. RESULTS: Median survival after salvage therapy of the recurrence was 37, 30 and 26 weeks, respectively. The HDR-BRT group did significantly better than both the reoperation (p<0.05) and the ddTMZ groups (p<0.05). Moderate to severe complications in the HDR-BRT, reoperation and sole chemotherapy groups occurred in 5/50 (10%), 4/36 (11%) and 9/25 (36%) cases, respectively. CONCLUSIONS: CT-guided interstitial HDR-BRT attained higher survival benefits in the management of recurrent glioblastoma after initial surgery and radiotherapy with concurrent temozolomide in comparison with the other treatment modalities. The low risk of complications of the HDR-BRT and the fact that it can be delivered percutaneously in local anaesthesia render it a promissing treatment option for selected patients which should be further evaluated.